SiskomEd as an Android Based Learning Media Solution to Support 21st Century Learning - Qurotul Aini; Vatmala, Viyayanti (SEAMEO SEAMOLEC, 2024)
Abstract In the process of teaching and learning activities, issues were identified regarding students' learning outcomes that did not meet the minimum standard grades. After conducting a simple observation, it was found that the low motivation of students and the lack of supportive learning facilities were the main reasons for the students' low grades. The research continued through several steps, including a) identifying the problem, b) analyzing and formulating the problem, c) planning the Classroom Action Research (CAR), and d) implementing the CAR. The identified issues were then analyzed, and a plan was made to carry out the CAR. In the Classroom Action Research activities, students were treated by providing them with Android-based learning media in the Computer Systems subject, named SiskomEd. Infrastructure issues such as internet connectivity problems were overcome by using SiskomEd offline. Additionally, utilizing Android-based learning media is one way to support 21st-century learning by leveraging technology. The research results showed that students experienced an improvement in grades after using the SiskomEd learning media in teaching and learning activities. The increase in grades was driven by the enhanced interest in learning among students. Students did not feel pressured during the learning process because the media used was engaging, colorful, and visually appealing. 21st-century learning media made students feel like they were playing while learning, leading to their enthusiasm to study the materials within it. Keywords: 21st-century learning, android-based learning media, SiskomEd, student interest in learning.